Pressure drop in "Velflo" pipe bends of one diameter throat radius: tests carried out by the College of Aeronautics for Wilmot Breeden Ltd - Chapman, C. S. (College of Aeronautics, 1961)
These tests were similar to those recorded in College of Aeronautics Note No. 95(2) by A. G. Smith, A. R. C. S. , B. Sc. , D. I. C. , and J. P. H. Webber, to which the reader is referred. This reo port gives experimental data for the pressure drop in "Velflo" pipe bends of 90 bend and one diameter throat radius. The bends were of 3" - 9" nominal diameter and the range was covered in steps of 1". Pressure drop data are provided in the form of pressure drop in the bends against nominal mean velocity for air of density 0.0763 lb/cu. ft. By "nominal mean velocity" is meant the mean velocity which would occur in a pipe of bore equal to the nominal for a given flow rate, and by "pressure drop" is meant the additional drop in pressure which occurs when a bend is inserted between two straight lengths. Both the bends and the pipes tested varied slightly in bore from the nominal diameter. Also given in the report is the non-dimensional form of the data, (useful in assessing consistency between the different tests) and the form of pressure drop against volume flow rate. This latter form is probably the most directly useful to customers of Wilmot Breeden Ltd.